Stomatal micromorphology in a complex of Mimosa section Mimosa (Fabaceae) - Grohar, Mariana Cecilia; Rosenfeldt, Sonia; Morales, Matias (Springer, 2021)
The genus Mimosa Linnaeus (Leguminosae) comprises more than 530 species, being one of the most diversified genera in the family. A vast morphologic variability has been described at all infrageneric levels. Considering stomata description, a very low proportion of species have been studied in the genus, and the description was limited to stomata types, but not to variation in the disposition of subsidiary cells. Here we analyze type, length, and distribution of stomatic complexes in 19 taxa of Mimosa subseries Dolentes and subseries Brevipedes, a high variability taxonomic complex, as well as their density on both foliar faces and epidermic pavement cell morphology. We found four different stomatal types, 2 distribution types, and 3 epidermic pavement cell shapes. Some of these features are taxonomically relevant at infraspecific levels, since it adds important information for the separation of the taxa, but also questions supraspecific taxonomic groups of previous proposals of the genus. We also hypothesized about the origin of the variation of some stomata features in relation to ecological and ploidy-level variability in this complex